A cross sectional study on self-medication practices among a selected rural community of Hooghly district, West Bengal - Taklikar, Chandrashekhar S.; Dobe, Madhumita (International Journal Of Community Medicine And Public Health, 2019)
Background: Medicines are often used incorrectly; around 50% of all medicines are prescribed, dispensed or sold inappropriately, while 50% of patients fail to take their medicines appropriately (WHO 2002). Self-medication is an important concern worldwide and WHO has laid emphasis on correctly investigating and controlling it. Self-medication practices have dramatically increased in the last few decades, especially in developing countries like India. Therefore, the present study was planned to assess the prevalence of self-medication for during acute illness episodes and factors associated among a rural community. Methods: The cross sectional study was conducted from February to March, 2017 in Anandnagar village, Singur block. All the 900 households in village were included in the study. Data regarding pattern of self-medication were collected by using pretested structured schedule from head of the family or next available adult member. Data were analysed by using Microsoft Excel 2016. Results: Amongst 900 household’s data could be collected from 864 households. Majority respondents were housewives in age group 40-60 years and primary educated. 50.7% respondents reported having acute illness among family members in past 3 months, 48.5% amongst them reported using self-medication. Cough (56.6%), fever (20.3%) and pain (11.2%) were the conditions for which self-medication was used. Nearby medicine shop was the source of self-medication among 59.3% respondents. 2.3% reported using old prescriptions. Conclusions:Half of the communities having acute illness were using self-medication. Uncontrolled use of medicines needs to be addressed as it brings potential health hazards, drug resistance and misuse.